SEASONAL INCIDENCE OF ANAR BUTTERFLY AND IT’S CORRELATION WITH WEATHER PARAMETERS - SAJAD MOHI-UD-DIN; N. A. WANI; M. JAMAL AHMAD; G. M. MIR; M. A. SOFI (The Bioscan, 2015)
The field data (pooled for 2011 and 2012) recorded on pest incidence of pomegranate fruit borer (Deudorix epijarbas) at major pomegranate growing places of Kashmir Valley revealed that the highest mean pest incidence (24.58 %) was recorded in Srinagar, followed by Budgam where mean incidence of (20.83 %) was recorded, while as, low mean incidence (19.63 %) of pest was recorded in Ganderbal. The pest starts its activity in the 2 nd fortnight of May and attained its peak in the 2 nd fortnight of August during 2011 with incidence of 49.66, 43.66 and 43.33 per cent observed in Srinagar, Budgam and Ganderbal, respectively. However, during 2012, peak was recorded in the I st fortnight of August with pest incidence of 53.00, 47.66 and 44.33 per cent recorded respectively in these districts.The maximum temperature, minimum temperature, maximum relative humidity, minimum relative humidity and rainfall and the population build up of the pest showed positive and significant correlation (r=0.7830, 0.8782, 0.7219, 0.7610 and 0.5643) and (r=0.6740, 0.9205, 0.7318, 0.5200 and 0.5293) during 2011 and 2012, respectively. Therefore, it can be concluded that fruit borer is causing a considerable damage to pomegranate fruits and also the weather factors extended their specific impact in building of borer population.